ADOPTED FOREIGNERS INHERITANCE BY INDONESIAN CITIZEN - Muhammet Ebuzer Ersoy (Jurnal Pembaharuan Hukum, 2019)
Adoption is governed by Law No. 23 of 2002 dated 22nd of Oct. 2002 concerning Child Protection; Decree of Minister of Social Affairs No. 44/HUK/1997 dated 31st of July 1997 concerning Fostering of ChildrenWelfare through Adoption; Decree of Minister of Social Affairs No. 2/HUK/1995 dated 25th of Jan. 1995 concerning Completion of Attachment of Decree ofMinister of Social Affairs No. 13/HUK/1993 concerning Implementation of Adoption; Supreme Court Circular Letter No. 2 of 1979 dated 7th of Apr. 1979concerning Adoption; and Supreme Court Circular Letter No. 6 of 1983 dated 30th of Sept. 1983 concerning Completion of Supreme Court Circular Letter No. 2 of 1979 concerning Adoption. An adoption is a legal act that distracts a child from the environment of its parents, legal guardian, or other people responsiblefor the care, education, and parenting, into a family environment with foster parents. It lawful both adoptions between Indonesian citizens and adoptionamong Indonesian citizens and foreigners. However, what is the legal consequences arising from the removal of the child? Is the adopted child could inherit fromtheir foster parents or not? Or is there a way to pass down an inheritance to adopted children who allowed the legislation? Therefore, this article will discuss.